PENGARUH SOCIAL MEDIA MARKETING DAN CONTENT MARKETING TERHADAP KEPUTUSAN PEMBELIAN PRODUK LUXCRIME PADA MARKETPLACE SHOPEE - Harisya Putri Oktavia; Noor Hidayati; Hairudinor; Novia Nour Halisa (Smart Business Journal (SBJ), 2025)
Harisya Putri Oktavia, 2010412120007, 2024. The effect of social media marketing and content marketing to purchasing decisions for Luxcrime products in the Shopee Marketplace, supervised by Noor Hidayati. This study sought to determine and assess the significant impact of Social Media Marketing and Content Marketing on the purchase decision of Luxcrime Produc in the Shopee Marketplace, both individually and in combination. This investigation utilized a quantitative methodology and concentrated on the Shopee marketplace user base of Luxcrime product consumers who made purchasing decisions. Non-Probability Sampling approach, specifically Pureposive Sampling technique, is used to select a few sample of 100 respondents. Data analvsis was conducted vsing Multiple Linear Regression analysis with the help of IBM SPSS Version 29.0, while data collection was done using questionnaires. Social media marketing has a partially significant impact on the purchase decision ot Luxcrime products in the Shopee marketplace, according to the research findings. In the same vein, the decision to purchase Luxcrime products in the Shopee marketplace is partially influenced by Content Marketing. Sales of Luxcrime products in the Shopee marketplace are significantly influenced by the combined effects of Social Media Marketing and Content Marketing.